A pan-cancer analysis of the oncogenic role of YKT6 in human tumors. Issue 15 (14th April 2023) - Zhang, Xuezhong; G. Dapar, Mark Lloyd; Zhang, Xin; Chen, Yingjun
Abstract : YKT6, as a Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein with vesicle trafficking, plays an essential role in the development and progression of tumor. However, the gene of YKT6 has not been fully assessed in pan-cancer studies. We aim to investigate the gene of YKT6 across 33 different types of tumor by using the Cancer Genome Atlas, Gene Expression Omnibus database, and other several kinds of bioinformatic tools. YKT6 is significantly up-regulated in most tumors, and we found that overexpression of YKT6 is positively associated with poor prognosis of overall survival and poor disease-free survival prognosis in several tumors, such as Adrenocortical carcinoma, Bladder Urothelial Carcinoma, Head and Neck squamous cell carcinoma. We also detected distinct associations exist between YKT6 and tumor mutational burden or microsatellite instability with tumors. YKT6 expression was positively related to cancer-associated fibroblasts for TCGA tumors of colon adenocarcinoma and LGG. Furthermore, we discovered a significantly positively correlation between YKT6 expression and endothelial cell in tumors of colon adenocarcinoma, HNSC-HPV+, OV, READ and THCA. While a negative relationship was obtained between YKT6 expression and endothelial cell in KIRC. Moreover, "Syntaxin binding, " "SNARE complex, " "vesicle fusion" and "DNA replication" are involved in the influence of YKT6 on tumor pathogenesis. Our pan-cancer analysis offers a deep comprehending the gene of YKT6 in tumoeigenesis from viewpoint of clinical tumor samples.